From Venice to the Nile Incredible journeys of the world - Fiocca,Richard (Franklin, TN Discover Magazine, 2015)
A series of three programs that take the viewer to different parts of the world, visiting Pompeii, Egypt, China, Australia, Ecuador, Alaska, and the Caribbean, surveying cultures and antiquities at various locales.
Incredible journeys From Venice to the Nile. From the Outback to Shangri-La From the Amazon to the Arctic
Documentary
Keywords: Voyages and travels; Pompeii (Extinct city) -- Description and travel; Pompeii (Extinct city) -- Antiquities; 1 videodisc (3 hr., 8 min.)